Oesophageal and gastric cancers: 8 years study inatertiary care hospital - Dr. Balkrishna Harishchandrarao Namdhari; Dr. Shubha Arvind Deshpande (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Gastric cancers are known for male preponderance. Aims and objectives: M: F ratio of oesophageal and gastric cancers and age group differences for comparison amongst both oesophageal and gastric sites of cancers. Materials and Methods: This is a retrospective and single institute study of oesophageal and gastric cancers diagnosed duringthe tenure of last 8 years. The histopathologically confirmed diagnosis of cancers of oesophageal and gastric sites selected. Results: 28 cases of oesophageal and gastric cancers selected during the tenure of last 8 years. The oesophagus cancers are less than gastric cancers > 27 % and age group for both sites are after 40 years only and more cases are seen in 40-50 age group in oesophagus and in 70-80 age groups in gastric cancers. M: F ratio for oesophagus cancers is 5.0 and for gastric cancers are 4.5. Metastatic age group is after 50 years of age in cancers of both oesophagus and gastric sites. Conclusion: Early diagnosis is the key to reduce the morbidity and mortality due to oesophageal and gastric cancers. Overall male predominance has been noted in the study. Histopathology is the most sensitive and specific diagnostic method for early detection of GI tract cancer which hasthe role in the diagnosis of gastrointestinal cancers and had aid in early management. Generation of population based data base is needed for the lesions diagnosed on gastric biopsy from different geographical regions of country. This helps in identification of spectrumof malignancies of oesophagus and stomach with early diagnosis and the improved survival of patients.